2019
DOI: 10.1007/s00264-019-04416-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of primary deltoid ligament repair in acute ankle fractures: a meta-analysis of comparative studies

Abstract: Purpose The indications of deltoid ligament repair in ankle injuries with widened medial clear space in the absence of medial malleolus fracture remain controversial. Many authors reported no difference in long-term functional outcomes, while others stated that persistent medial clear space widening and malreduction are higher when deltoid ligaments went without repair. This meta-analysis aims to report the current published evidence about the outcomes of deltoid ligament repair in ankle fractures. Methods Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…Woo et al [23] noted that without DL repair, patients occasionally suffered from persistent medial pain around the DL even after anatomical healing. Some authors believe DL repair will prolong the operation and increase the incidence of wound-related complications [32], and our data analysis shows the same results.…”
Section: Plos Onesupporting
confidence: 81%
“…Woo et al [23] noted that without DL repair, patients occasionally suffered from persistent medial pain around the DL even after anatomical healing. Some authors believe DL repair will prolong the operation and increase the incidence of wound-related complications [32], and our data analysis shows the same results.…”
Section: Plos Onesupporting
confidence: 81%
“…In addition, a number of studies have shown that approximately 40% of patients treated for ankle instability display DL injury. Although some researchers continue to dispute whether such DL injuries should be repaired, some believe that the quality of life of patients is unaffected in the absence of a repair [ 31 , 32 ]. Therefore, we aimed in the present study to explore whether joint injury from transection of the CL+ATFL or CL+DL ligaments affected ankle-subtalar joint complex instability, ultimately reducing the quality of life of a patient, and to provide an updated reference for clinical treatments of ankle-subtalar joint complex instability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review available on this topic including only 3 prospective studies (1 level 2, 2 level 3 studies) with small sample size, did not prove the superiority of additional medial repair [10]. An important part of this discussion may be the switch from screw fixation to flexible systems.…”
Section: The Deltoid Ligament Dilemma: To Repair or Not To Repair?mentioning
confidence: 98%